2002
DOI: 10.1080/135502802317247785
|View full text |Cite
|
Sign up to set email alerts
|

Infection of human oligodendroglioma cells by a recombinant measles virus expressing enhanced green fluorescent protein

Abstract: One of the hallmarks of the human CNS disease subacute sclerosing panencephalitis (SSPE) is a high level of measles virus (MV) infection of oligodendrocytes. It is therefore surprising that there is only one previous report of MV infection of rat oligodendrocytes in culture and no reports of human oligodendrocyte infection in culture. In an attempt to develop a model system to study MV infection of oligodendrocytes, time-lapse confocal microscopy, immunocytochemistry, and electron microscopy (EM) were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…It should be noted that signaling lymphocyte-activation molecule (SLAM) is considered the main receptor for some wild-type strains of MV, while CD46 is used preferentially by vaccine strains and certain other wildtype strains (Schneider-Schaulies et al, 1995). However, because SLAM is not expressed by brain cells (McQuaid and Cosby, 2002;Plumb et al, 2002) other mechanisms are responsible for MV spread in the CNS. It has been shown that a single amino acid substitution in the sequence of HA (from asparagine or lysine to tyrosine in position 481) allows wild-type strains of MV to interact with CD46, while preserving the ability to bind SLAM (Buckland and Wild, 1997).…”
Section: Resultsmentioning
confidence: 97%
“…It should be noted that signaling lymphocyte-activation molecule (SLAM) is considered the main receptor for some wild-type strains of MV, while CD46 is used preferentially by vaccine strains and certain other wildtype strains (Schneider-Schaulies et al, 1995). However, because SLAM is not expressed by brain cells (McQuaid and Cosby, 2002;Plumb et al, 2002) other mechanisms are responsible for MV spread in the CNS. It has been shown that a single amino acid substitution in the sequence of HA (from asparagine or lysine to tyrosine in position 481) allows wild-type strains of MV to interact with CD46, while preserving the ability to bind SLAM (Buckland and Wild, 1997).…”
Section: Resultsmentioning
confidence: 97%
“…These include reovirus as well as members of the Paramyxovirus and Orthomyxovirus families, consisting of measles virus, Newcastle disease virus, mumps and influenza viruses (28,33,35,36,38,48,57,66,70,76,78,80,95). Even Picornaviruses, such as poliovirus, have been demonstrated to exert oncolytic effects, as well as cytolytic replicating RNAs derived from alphaviruses (3,32,94,95).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to neurones, MV antigen ( Figure 1A) and RNA is present in oligodendrocytes and, to a lesser degree, in astrocytes and endothelial cells in SSPE brain (Kirk et al, 1991;Plumb et al, 2002). Viral RNA and antigen are also present in inflammatory cells in perivascular cuffs (Cosby et al, 1989;Allen et al, 1996).…”
Section: Neuropathology Of Morbillivirus Infectionsmentioning
confidence: 96%